Factors That Affect the Efficiency of the Internal Control System of Agencies Under Phra Nakhon Si Ayutthaya Provincial Public Health Office - วงศ์ทองคำ, สมพร (Journal of Preventive Medicine Association of Thailand, 2018)
This research is analytical cross-sectional study. This study aims to investigate factors that affect the efficiency of the internal control system of agencies under Phra Nakhon Si Ayutthaya Provincial Public Health Office. All data were collected by using a level cognitive system control of self-assessment questionnaire and the internal control questionnaire based on the concept of The Committee of Sponsoring Organizations of the Treadway Commission (COSO.), which collected data from the sample consisted of 125 internal audit officers under Phra Nakhon Si Ayutthaya provincial public health office Statistics used to analyze the data was Stepwise Multiple Regression Analysis. The findings were concluded that the cognitive self-assessment level used in the operation of internal control (self-assessment: CSA) and obtaining knowledge about the internal audit and internal control were the factors that affect the efficiency of the internal control system of agencies under Phra Nakhon Si Ayutthaya Provincial Public Health Office. Statistical significance was (p-value<.001), with the factors predicting (R2) equal .25 and .14 respectively. Work period and work experience in internal audit and internal control were the factors that affect the efficiency of the internal control system of agencies under Phra Nakhon Si Ayutthaya Provincial Public Health Office was not statistically significant (p-value .08), with the factors predicting (R2) as .00 Gender, age, marital status, education level, and position cannot predict the factors that affect the efficiency of the internal control system of agencies under Phra Nakhon Si Ayutthaya Provincial Public Health Office.